SH Tingkat Serangan Hama Kutu Hijau (Coccus viridis) Pada Tanaman Kopi di PT PTL Coffee Bean di Kabupaten Solok Selatan - Annisa Fitri Ramadhani; Sri Heriza; Muhammad Parikesit Wisnubroto (BPFP Universitas Bengkulu, 2025)
[[INFESTATION LEVEL OF GREEN SCALE INSECT (Coccus viridis) ON COFFEE PLANTS AT PT PTL COFFEE BEAN, SOLOK SELATAN REGENCY]. The green scale insect (Coccus viridis) is a major pest in coffee plantations in Indonesia. It is classified as an economically significant pest due to its potential to cause up to 50% plant damage, leading to substantial yield reduction and financial losses. This study aims to determine the infestation level of Coccus viridis at PT PTL Coffee Bean, Solok Selatan Regency, and to analyze the influence of environmental factors on infestation intensity. The findings of this study are expected to serve as a foundation for developing appropriate pest control strategies based on the principles of Integrated Pest Management (IPM). The research was conducted using a systematic sampling method with a diagonal line pattern across the coffee plantation owned by PT PTL Coffee Bean. Direct field observations were performed, and further analyses were conducted at the Integrated Pest Management Laboratory, Faculty of Agriculture, Andalas University. The results showed that the infestation intensity of Coccus viridis on coffee plants at the study site was 15.38%, which falls into the mild infestation category. The infestation level was influenced by environmental factors such as altitude, temperature, humidity, light intensity, and cultivation techniques. Although the infestation level was classified as mild, regular monitoring remains essential to prevent an increase in pest populations. Furthermore, IPM-based control strategies should be optimized to sustain coffee plant productivity, including the conservation of natural enemies and the application of proper cultivation techniques.